The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1124/dmd.120.000086
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Tiered In Vitro Approach to De-Risk Drug Candidates for Potential Bile Salt Export Pump Inhibition Liabilities in Drug Discovery

Abstract: Hepatocellular accumulation of bile salts by inhibition of bile salt export pump (BSEP/ABCB11) may result in cholestasis and is one proposed mechanism of drug induced liver injury (DILI). To understand the relationship between BSEP inhibition and DILI, we evaluated 64 DILI positive and 57 DILI negative compounds in BSEP, multidrug resistance protein 2 (MRP2), MRP3, and MRP4 vesicular inhibition assays. An empirical cutoff (5 μM) for BSEP inhibition was established based on a relationship between BSEP IC 50 val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Major publications from both the industry and the International Transporter Consortium have recommended the testing of BSEP inhibition. The relevant papers with suggested cut-off values [ 143 , 144 , 145 , 146 , 147 , 148 , 149 ] are summarized in Table 1 . Most studies employ a vesicular transport assay with taurocholate as a probe, albeit some cholestatic compounds have been shown to act via repression of BSEP expression, which can only be investigated in cellular models [ 150 ].…”
Section: In Vitro Test Systems For the Study Of Bile Acid/bile Salt T...mentioning
confidence: 99%
See 4 more Smart Citations
“…Major publications from both the industry and the International Transporter Consortium have recommended the testing of BSEP inhibition. The relevant papers with suggested cut-off values [ 143 , 144 , 145 , 146 , 147 , 148 , 149 ] are summarized in Table 1 . Most studies employ a vesicular transport assay with taurocholate as a probe, albeit some cholestatic compounds have been shown to act via repression of BSEP expression, which can only be investigated in cellular models [ 150 ].…”
Section: In Vitro Test Systems For the Study Of Bile Acid/bile Salt T...mentioning
confidence: 99%
“…For compounds in the discovery phase where the C plasma values are still only predicted and may thus be unreliable, risk assessment can be based solely on IC 50 , and different groups have suggested cut-off values of 25 [ 145 ] and 50 µM [ 147 ]. Aleo et al have applied a complex scoring system, with the highest score (most severe category) assigned to compounds with IC 50 /C max,total ≤ 1 and the safe zone for BSEP inhibition starting at IC 50 /C max,total > 100 [ 148 ]. In other studies, the utility of in vitro BSEP inhibition for predicting DILI has been confirmed without recommending a specific cut-off [ 96 , 108 ].…”
Section: In Vitro Test Systems For the Study Of Bile Acid/bile Salt T...mentioning
confidence: 99%
See 3 more Smart Citations